Papua New Guinea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper provides an overview of financial access and inclusion indicators, related causal factors, and both current and possible reform priorities for on Papua New Guinea (PNG). The paper presents indicators of financial market depth, development, and access for PNG and compares PNG's performance against that of other countries in the region, at similar levels of development, and beyond. It provides an overview of country-specific challenges facing PNG related to financial inclusion that helps to explain its performance, as well as possible reform priorities in the near term. The government's current initiatives aimed at promoting financial sector development and inclusion and their preliminary results are also discussed.